Olanzapine enabled rechallenge after lorlatinib‐induced psychosis: A case report - Akiyoshi Yokode; Masaki Fujiwara; Yuko Nakamura; Kadoaki Ohashi; Shinji Sakamoto; Manabu Takaki (PCN Reports, 2025)
Abstract Background Lorlatinib is a third‐generation tyrosine kinase inhibitor for anaplastic lymphoma kinase (ALK)‐positive non‐small cell lung cancer (NSCLC). While it has a high intracranial lesion control rate, it can also cause central nervous system complications, including psychotic symptoms. We present a case of lorlatinib‐induced psychosis successfully managed with olanzapine, enabling lorlatinib rechallenge. Case Presentation A 32‐year‐old woman with ALK‐positive NSCLC and brain metastases was started on lorlatinib. After 18 months, she developed hallucinations and delusions. Despite treatment with risperidone, her psychotic symptoms persisted, leading to hospitalization. Her symptoms resolved upon lorlatinib discontinuation while risperidone was continued. Given the critical role of lorlatinib in controlling brain metastases, rechallenge was considered. To mitigate concerns regarding drug interactions, risperidone was replaced with olanzapine. Following lorlatinib rechallenge with olanzapine, no recurrence of psychiatric symptoms was observed, allowing continued lorlatinib treatment. Additionally, no progression of lung cancer was noted. Conclusion Lorlatinib is an essential drug for controlling brain metastases in ALK‐positive NSCLC. However, it can induce psychotic symptoms. When psychiatrists are involved in managing adverse effects during cancer treatment, close collaboration among oncologists, psychiatrists, and patients is essential.